(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2012)
An existential-phenomenological approach was applied in a study exploring the experience of participating in physical activity when living with a disability. Findings suggest that physical activity can have an existential meaning, and influence the way participants experience their own body and abilities. This constitutes an aspect which is seldom explored in research concerning the challenges of living with a disability.